Prevalence, trends, and specialized palliative care utilization in Taiwanese children and young adults with life-limiting conditions between 2008 and 2017: a nationwide population-based study - Shih-Chun Lin; Mei-Chih Huang (BMC, 2024)
Abstract Background Previous studies have shown a growing need for pediatric palliative care, but there is a lack of knowledge in many countries concerning prevalence of service use among children and young adults with life-limiting conditions. This study aimed to estimate (1) the annual prevalence of children and young adults with a life-limiting condition, and (2) their specialized palliative care and other healthcare utilization. Methods Data from the Health and Welfare Data Science Center in Taiwan were used. All children and young adults aged 0-25 years recorded in inpatient or outpatient data, and infants aged < 1 year in death data with a life-limiting condition diagnostic code from 2008 to 2017 were recruited. Poisson regression was used to estimate the crude and adjusted relative risk of prevalence of life-limiting conditions with 95% confidence intervals, adjusted for age and sex, and to evaluate the trend in prevalence of each life-limiting diagnostic groups, in specialized palliative care and other service use. Results Data contained 236,250 individuals with a life-limiting condition, of which oncological and congenital abnormalities were the most common. There was an annualized increase over 10 years in the prevalence of life-limiting conditions of 36.4%, from 45,311 cases (59.4 per 10,000 population) to 52,226 cases (81.0 per 10,000 population), with the highest prevalence in individuals aged 21-25 years. All diagnostic groups showed significant increases in prevalence (p < .001) with the exception of oncology, circulatory, and "other" group. Specialized palliative care services, including family consultation, shared care, home visits have increased in use over time (p < .001), while inpatient hospice has slightly decreased. The highest prevalence of healthcare use was for traditional Chinese medicine (237.1 per 1,000 population in 2017), but this decreased over time (p < .001). Conclusions Due to a growing trend towards multidisciplinary care, healthcare professionals and policymakers must engage and take action to expand specialized palliative care and integrate delivery of other healthcare services. Traditional Chinese medicine having a decreasing slope, yet still the highest prevalence of use, needs further attention.